Strategi Pemerintah Kota Tanjungpinang dalam Upaya Penurunan Angka Kematian Ibu - Lia Ulvi Miranata Putri; Afrizal Afrizal; Eki Darmawan (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
The maternal mortality is an obstacle in efforts to develop human resources because it can reduce the level of maternal health and community welfare. Cases of maternal deaths in Tanjungpinang City in 2023 have increased compared to 2022, bringing the total to six deaths. Problem in the health sector cannot be separated from the affairs of the regional government, in this case through the Tanjungpinang City Health, Population Control, and Family Planning Service. This research aims to analyse the strategies carried out by the Tanjungpinang City Government in efforts to reduce maternal mortality using Strategy Theory by Geoff Mulgan. The research method used was a qualitative research method with a case study approach was and a total of 11 informants. Data collection techniques were carried out using interviews and documentation and analysed by data collection, data reduction, and data presentation. The research results show that the Tanjungpinang City Government in 2023 has carried out activities related to efforts to reduce maternal mortality in accordance with its vision and mission. This activity involves the Community Health Centre and parties in the field to ensure that pregnant women are monitored and follow the directions given. The challenges faced by the Tanjungpinang City Government with the high maternal mortality in 2023 are the lack of knowledge of pregnant women regarding pregnancy, the low level of delivery which is not carried put in health facilities, and the lack of empowerment of families and communities regarding the KIA Book. Overall, the strategy implemented by the government must be supported by the role of the community as the recipient of the strategy so that the high maternal mortality rate in Tanjungpinang City in 2023 means that the reduction has not been optimal due to a lack of knowledge and community awareness.